ENDOSCOPIC AND ENDOSURGICAL TREATMENT OF CHOLEDOCHOLITHIASIS (World Bulletin of Public Health, 2023)
Our first experience with the use of our developed papillotomes in patients with calculous cholecystitis, choledocholithiasis, and DSFS shows the prospects of this technique
Keywords: Cholelithiasis; Laparoscopic cholecystectomy; endoscopic papillosphincterotomy